NATIVE LANGUAGE INTERFERENCE IN LEARNING ENGLISH - Djabbarova Sh.B.; Isomiddinova Z. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article discusses the phenomenon of phonetic interference, which includes such processes as stress, intonation, and pronunciation. Phonetic interference is a significant problem for Uzbek students, as Uzbek and English belong to different language families. Additionally, the specific phonetic sounds of the Uzbek language create difficulties in learning English pronunciation, which leads to communication barriers and misunderstandings. The article aims to examine the differences in the special phonetic letters between English and Uzbek languages that cause the interference phenomenon, and proposes useful strategies to solve these problems. In this article, the problems related to this topic will be introduced and provided solutions.